Carbon nanotube sorting due to commensurate molecular wrapping. Issue 29 (17th July 2020) - Konevtsova, Olga V.; Roshal, Daria S.; Dmitriev, Vladimir P.; Rochal, Sergei B.
Abstract : Commensurate wrapping of carbon nanotubes ensures their selection by flavin group molecules. Abstract : Single-walled carbon nanotubes (SWCNTs) can be sorted by their structural parameters using organic molecules and polymers: some of which, demonstrating a profound affinity only for specific nanotubes, form dense coatings on them. Here, analyzing well-known examples of flavin group molecules and those of 2, 4-dichlorophenoxyacetic acid, we show for the first time that successful formation of the considered coatings depends on the ability of molecules to wrap around the SWCNT in a commensurate way. Commensurability provides a decrease in the free energy of the resulting bilayer system and makes the coating much more stable. Concurrently, it strongly relates the nanotube chiral vector with the geometric characteristics of the adhering molecules, which leads to revealed selection rules. If they are not satisfied, the deposition of molecules does not occur or is insignificant. The proposed theory unambiguously explains known experimental results on the formation of spiral wrappings of SWCNTs by flavin group molecules and points out other organic molecules and polymers suitable for effective CNT sorting.